“COVID-19 and Pregnancy: A Compelling Need for Vaccination" - Naeem, Unaiza; Syed Hasan Shuja; Jawed, Areesha (Journal of the Pakistan Medical Association, 2022)
Madam, Since the beginning of 2021, massive vaccination programmes have been initiated, aiming to curb the COVID-19 pandemic, yet certain groups remain vulnerable, especially pregnant women (1). A recent study has emphasized the implications of COVID-19 in pregnant females; evaluating statistics from various countries, the authors reported maternal mortality to be 22 times higher in pregnant women with COVID-19 diagnosis than those without (2). Compared with those without COVID-19, infected females giving birth showed significantly higher rates of ICU admission, respiratory intubation, mechanical ventilation, and a greater risk of having a preterm birth of fewer than 37 weeks (2). In Pakistan, Covid-19 is speculated to cause multiple complications among unvaccinated pregnant women. When local data was collected and presented at a webinar “Pregnancy in Covid-19 and importance of vaccine” held by a public medical university in association with the American Society of Microbiology, it was highlighted that Covid-19 caused a death rate of 8% in pregnant women. Each year, approximately 14% of pregnant women are susceptible to have medical complications. (3) These adverse outcomes during pregnancy accentuate the need for vaccination of pregnant individuals. Recent studies have started assessing the outcome of Covid-19 vaccination on the pregnant women population and demonstrated positive results. Blakeway et al reported that women who received at least one dose of COVID-19 vaccine in pregnancy versus unvaccinated females had similar rates of all adverse pregnancy outcomes and concluded that vaccines do not affect perinatal outcomes (4). Guidelines recommending urgent vaccination for pregnant people have also been released, stressing that the benefits of the vaccine supercede any potential risks (1). However, several factors have hindered the process of vaccination of pregnant women such as the exclusion of pregnant women from clinical trials that have caused difficulty in establishing confidence of pregnant women in the vaccines In addition, the prevailing conspiracy theories in Pakistan about vaccination programmes, being a Western agenda to induce sterility in Muslim women has further hindered the success of vaccination programme for pregnant women. (5) Physicians must implement the past positive findings of vaccination among pregnant women when counseling patients who are pregnant, planning a pregnancy, breastfeeding, or planning to breastfeed, and facilitate them in opting for government authorized vaccines for clinical use. At the same time, pregnant women who wish to wait for more data to make an informed decision must be supported and updated by their doctor regularly. ---continue